The Causal Relationship Between Rheumatoid Arthritis and Mechanical Complications of Prosthesis After Arthroplasty: A Two-Sample Mendelian Randomization Study - Cai, Yuanqing; Zhang, Guangyang; Liang, Jialin; Jing, Zhaopu; Zhang, Rupeng; Lv, Leifeng; Dang, Xiaoqian (Frontiers in Genetics, 2022)
The causal effects of rheumatoid arthritis (RA) on complications of arthroplasty are yet to be established. This study was the first to explore the causal effect of RA on mechanical complications of prosthesis through two-sample Mendelian randomization (MR). In the MR analysis, RA was selected as the exposure in this study while single-nucleotide polymorphisms (SNPs) from a genome-wide association study (GWAS) were selected as the instrumental variables (IVs). Summary statistics data on mechanical complications of prosthesis was extracted from publicly available GWAS data, including 463,010 European descent individuals. MR analysis was performed using the standard inverse variance weighted (IVW). Furthermore, other methods (MR Egger, Weighted median, Simple mode, and Weighted mode) were also done to verify the results. Finally, the sensitivity analysis was executed. Results of the standard IVW showed that RA possibly increases the risk of mechanical complications of prosthesis [OR=1.000255; 95% CI=(1.0001035, 1.000406); P=9.69×10-4]. This outcome was also verified by other methods including weighted median [OR=1.000285; 95% CI=(1.0001032, 1.000466); P=1.41×10-3], simple mode [OR= 1.000446; 95% CI=(1.0001116, 1.000781); P=1.04×10-2], and weighted mode [OR= 1.000285; 95% CI=(1.0001032, 1.000466); P=2.29×10-3]. No heterogeneity and directional pleiotropy was observed upon sensitivity analysis, indicating the stability and reliability of the result. In summary, the present study showed that RA potentially increases the risks of complications of prosthesis, which might provide guidance in arthroplasty on RA patients.